LARGE TIME BEHAVIOR OF A THIRD GRADE FLUID SYSTEM - 柴晓娟 陈正争 钮维生 (Acta mathematica scientia, 2016)
We consider the large time behavior of a non-autonomous third grade fluid sys- tem, which could be viewed as a perturbation of the classical Navier-Stokes system. Under proper assumptions, we firstly prove that the family of processes generated by the problem ad- mits a uniform attractor in the natural phase space. Then we prove the upper-semicontinuity of the uniform attractor when the perturbation tends to zero.